FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP HIPERTENSI PADA USIA PRODUKTIF DI WILAYAH KERJA PUSKESMAS SUMANDA KECAMATAN PUGUNG KABUPATEN TANGGAMUS - nur hasanah nur hasanah; eti ardiani ardiani (Viva Medika, 2017)
Hypertension can affect all ages including the age of production. There are 600 million people with hypertension worldwide or 1 in 3 adults suffering from hypertension. One of the causes is poor lifestyle such as rarely exercising, stress and unhealthy eating patterns. The purpose of the study to know the factors that affect the incidence of hypertension in productive age in the working area of â€‹â€‹Puskesmas Sumanda. This research uses analytic survey method with cross sectional study approach. The population in this study is 642 people of productive age. Based on the sampling technique using purposive sampling, the sample of 87 respondents was obtained. This study used univariate, bivariate and multivariate analysis. The result of statistical test using chi square shows. The existence of relationship of age with incidence of hypertension at productive age (Ï value = 0,014): there is relation of sex with incidence of hypertension at productive age (Ï value = 0,004), there is relationship of sport behavior with hypertension occurrence at productive age (Ï value = 0,002) , there is a relationship of stress with the incidence of hypertension in the productive age (Ï value = 0.020). There is a relationship of sodium consumption with the incidence of hypertension at the productive age (Ï value = 0.010). There is no relationship of fat consumption with the incidence of hypertension in productive age (Ï value = 0.068). The result of multiple logistic regression test shows that sport factor has the most influential risk (POR = 17,73) with the happening of hypertension. Conclusion: Factors of age, sex, exercise behavior, stress, sodium consumption is a factor that affects the incidence of hypertension. Keywords: factors, hypetension, Productive age Reference: 43 (2010 - 2016)